Development of two reverse transcription‐PCR methods to detect living pinewood nematode, Bursaphelenchus xylophilus, in wood. Issue 2 (20th September 2012) - Leal, I.; Foord, B.; Allen, E.; Campion, C.; Rott, M.; Green, M.; Sturrock, R. N.
Summary Pinewood nematode, Bursaphelenchus xylophilus, is an inhabitant of native pine species of North America, where its presence in trees is non‐pathogenic. By contrast, the introduction of this nematode to forests overseas has devastated some pine stands and is recognized as a pest of phytosanitary concern by some countries' National Plant Protection Organizations. The ability to detect B. xylophilus in internationally traded wood products is crucial to reduce the spread of this organism. Current molecular techniques for the detection of B. xylophilus rely on the presence of genomic DNA and thus will detect both living and dead nematodes without differentiation. The detection of dead nematodes could lead to unnecessary trade disruption. Therefore, accurate techniques for the detection of and differentiation between live and dead B. xylophilus are critical. We have developed an endpoint RT‐PCR assay and a SYBR Green 1 real‐time RT‐PCR assay, both of which selectively identify living pinewood nematode by detecting the presence of Hsp70 mRNA as a viability marker. Both of these assays may help overcome or resolve disputes involving the detection of pinewood nematode at the port of entry and can also be used to evaluate the efficiency of wood treatment procedures.